INFLUENCE OF APPLICATION OF STEM LEARNING MODEL WITH SOSIOEMOTIONAL APPROACH TO IMPROVE LOGICAL THINKING ABILITY - Luluk Fuadah; Ulum Fatmahanik (Science Education, Institut Agama Islam Negeri Ponorogo, 2022)
The ability to think logically is one of the complex skills of the 21st century that is important to prepare for the world of work. But in fact students' logical thinking skills tend to be low because the learning model applied by the teacher tends to be monotonous so that understanding of the material and student activity becomes less. The STEM learning model with the socioemotional approach is one model that can solve these problems because it is an innovative learning model that is also integrated from several socioemotional-based disciplines that emphasizes student activity and is based on real-world problems so that it is suitable for improving logical thinking skills. This study aims to determine the relationship between the STEM learning model and the socioemotional approach in improving logical thinking skills. This research uses quantitative method with Quasi Experimental Design research type . Data were obtained from class VIII MTs Ma'arif Al-Mukarrom through observation and tests. The instruments used are learning tools (syllabus, lesson plans, and LKPD), observation sheets of student activities and implementation, and written tests of logical thinking skills. Data analysis using T test and N-Gain. The results showed that the implementation of the STEM learning model with a socioemotional approach was 89.50% and student activity was 90.84% in very good criteria. The T test results show a significance of 0.003 less than 0.005 so it can be concluded that there is a significant effect between the STEM learning model with the Socioemotional approach in improving logical thinking skills, also the N-Gain Test proves that the STEM learning model with the Socioemotional approach is more effective than the conventional model in improving logical thinking skills.